Stereoselective C-X and regioselective C-H activation to, and selective C(sp2)-C(sp3) reductive elimination from, platinum compounds with thiophene-derived ligands. Issue 43 (24th October 2019) - Anderson, Craig M.; Brown, Garrett; Greenberg, Matthew W.; Yu, David; Bowen, Nellie; Ahmed, Rahma; Yost-Bido, Melissa; Wray, Alina
Graphical abstract: Highlights: Regioselective cyclometalated platinum complexes with five-membered rings have been synthesized and characterized. DFT calculations have been performed to support observation of platinum(IV) isomers. Small degree of stereoselectivity is observed for oxidative addition of C-Br bonds. Abstract: Several thiophene-based N^C ligands were synthesized. Strategically, a bromide was incorporated on the 2-position of the thiophene ring. When allowed to react with the platinum tetramethyl dimer, [Pt2 Me4 ( µ -SMe2 )2 ], platinum(IV) platinacycles were formed by oxidative addition of the C(sp 2 )-X bond. These platinum(IV) compounds were characterized by NMR and HRMS. The platinum (IV) compounds were subsequently subjected to thermolysis. A series of reactions occurred, including selective C-C reduction elimination and selective C-H oxidative addition, giving mixtures of platinum(II) products with varying degrees of regioselectivity.